Analisis Yuridis Terhadap Upaya Hukum Pembelaan Advokat Terhadap Tersangka Korupsi Yang Menghalang-Halangi Penyidikan KPK (Studi Putusan No. 09/Pidsus-TPK/2018) - Taufiq Nugraha Syahputra; Edi Warman; Edi Yunara; M Hamdan (Universitas Medan Area, 2021)
This study aims to analyze the position of advocates in carrying out their duties and obligations as part of law enforcement in Indonesia, and to examine the factors that cause advocates to hinder legal actions in investigating corruption crimes carried out by KPK investigators. As well as to examine criminal liability for the actions of advocates that hinder the investigation, prosecution and trial of perpetrators of corruption. This research is a normative legal research. With the nature of descriptive analytical research. This research was conducted using library research and qualitative data analysis. This study also uses interview guidelines as a data collection tool. This study resulted that the SN corruption crime committed by FY advocates in the Central Jakarta District Court Decision No. 09/Pidsus-TPK/2018 in the investigation process carried out by the KPK investigators was hampered, so that the investigation time could be extended and could delay the legal process. The prosecution and trial of the criminal act of corruption is an effort by FY advocates to save suspect SN from the snares of legal prosecution by the Public Prosecutor Criminal responsibility for the actions of lawyers who hinder the investigation, prosecution and trial of perpetrators of criminal acts of corruption is that the act is against the law of Article 21 of Law No. 20 of 2001 concerning amendments to Law No. 31 of 1999 concerning the Eradication of Criminal Acts of Corruption